2019
DOI: 10.1016/j.ijantimicag.2019.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Hot topics on vertebral osteomyelitis from the International Society of Antimicrobial Chemotherapy

Abstract: Vertebral osteomyelitis (VO), also known as spondylodiscitis, describes infections of the vertebrae and intervertebral discs. Discitis describes infection limited to the intervertebral discs; in clinical practice both discitis and VO can be regarded as different stages of a single entity. VO can be caused by bacteria, fungi and parasites The incidence of VO is increasing globally representing 3-5% of all osteomyelitis with an estimated incidence ranging from 4 to 24 per million per year. Increasing incidence h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 70 publications
4
37
0
Order By: Relevance
“…In the literature, the sensitivity of image-guided biopsy in evaluated studies is about 40% (Sehn and Gilula, 2012 an infection that is very difficult to diagnose and treat, considering also the high rate of patients on antibiotic therapy at the time of diagnosis. The latter results in a low rate of positivity for BC and vertebral biopsy to determine the etiology of infection (Saeed et al, 2019). As reported in Figure 2, vertebral biopsy without antimicrobial discontinuation, according to the protocol, was associated with a high rate of negative results in the present study.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In the literature, the sensitivity of image-guided biopsy in evaluated studies is about 40% (Sehn and Gilula, 2012 an infection that is very difficult to diagnose and treat, considering also the high rate of patients on antibiotic therapy at the time of diagnosis. The latter results in a low rate of positivity for BC and vertebral biopsy to determine the etiology of infection (Saeed et al, 2019). As reported in Figure 2, vertebral biopsy without antimicrobial discontinuation, according to the protocol, was associated with a high rate of negative results in the present study.…”
Section: Discussionsupporting
confidence: 54%
“…In this study population, failure of therapy for VO was observed in 19 patients (14.3%). The failure rate of patients treated for VO in most clinical studies has varied between 10% and 30% (Berbari et al, 2015;Ohtori et al, 2010;Hungenbach et al, 2013;Sehn and Gilula, 2012;Bhavan et al, 2010;Saeed et al, 2019;Kowalski et al, 2007;Zarrouk et al, 2007;Carragee, 1997;Nanni et al, 2012;Kim et al, 2009;Bassetti et al, 2017;Bakheet et al, 1998;Trecarichi et al, 2012;Heysell et al, 2013;Rissing, 1997). The therapeutic management of VO patients with treatment failure should be tailored to the suspected reason for failure.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging should include the entire spine in order to assess the extension of the infection and to exclude any adjacent or skip lesions. Bone scintigraphy with technetium or labelled leucocytes is not routinely indicated because of their low sensitivity and specificity; gallium scans can have a role because if the result is negative, osteomyelitis is unlikely [45]. Newer tracers for bone scintigraphy such as indium-111 labeled (111In) biotin and streptavidin have been recently introduced [46].…”
Section: Diagnosismentioning
confidence: 99%
“…Although there is a wide range of bacteria that can cause spinal infections, in most cases these infections are caused by a single microorganism rather than from multiple pathogens [45]. In those few poly-microbial infections (<10% of cases), the spine is usually affected through contiguous spread [30].…”
Section: Microbiologymentioning
confidence: 99%
See 1 more Smart Citation